Values and Revaluations The Transformation and Genesis of 'Values in Things' from Archaeological and Anthropological Perspectives - Hahn, Hans Peter; Klöckner, Anja (Oxbow Books, 2023)
Why are some things valuable while others are not? How much effort does it take to produce valuable objects? How can one explain the different appraisal of certain things in different temporal horizons and in different cultures? Cultural processes on how value is attached to things, and how value is re-established, are still little understood. The case studies in this volume, originating from anthropology and archaeology, provide innovative and differentiated answers to these questions. However, for all contributions there are some common basic assumptions. One of these concerns the understanding that it is rarely the value of the material itself that matters for high valuation, but rather the appreciation of the (assumed or constructed) origin of certain objects or their connection with certain social structures. A second of these shared insights addresses the ubiquity of phenomena of 'value in things'. There is no society without valued objects. As a rule, valuation is something negotiated or even disputed. Value arises through social action, whereby it is always necessary to ask anew which actors are interested in the value of certain objects (or in their appreciation). This also works the other way round: Who are those actors who question corresponding objective values and why?